Donor-Acceptor Azulenes with Intense Absorption and Emission in the Visible Region - Merkhatuly, Nurlan; Iskanderov, Amantay; Iskanderov, Ablaykhan; Abeuova, Saltanat; Zhokizhanova, Saltanat (SynOpen, 2025)
New donor-acceptor compounds based on the azulene nucleus have been synthesized that demonstrate intense light absorption in the visible spectrum (380–600 nm) and emit light in the blue photoluminescence range. The appearance of photoluminescence is a unique feature of the resulting compounds and is absent from the original azulene. This ability was achieved by introducing a donor substituent at position 2 and acceptors at positions 1 and 3 of azulene. This led to a restructuring of its electronic structure, which created the prerequisites for the permitted π-π* transition.
Keywords: azulene; azulenecarbonitrile; donor-acceptor azulene; carbazolyl-azulene; optoelectronics; photoluminescence